2017
DOI: 10.5588/ijtld.17.0049
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of active case finding for tuberculosis and HIV at the household level in slums in Haiti

Abstract: SUMMARY Setting Haiti has the highest burden of tuberculosis (TB) in the Americas, with an estimated prevalence of 254/100,000 population. GHESKIO conducted active case finding (ACF) for TB at the household level in nine slums in Port-au-Prince. Objective We report on the prevalence of undiagnosed TB detected through GHESKIO’s ACF campaign. Design From August 1, 2014 to July 31, 2015, we conducted a retrospective cohort analysis using GHESKIO’s ACF campaign data. All individuals who reported chronic cough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…GHESKIO was founded in 1982 and is the largest provider of integrated services for HIV and tuberculosis in Haiti. Over the past 35 years, GHESKIO has provided community health interventions in these slum communities including HIV testing, tuberculosis screening, and cholera vaccination [15][16][17]. The study population includes 4 slums: Village de Dieu, Cité Plus, Cité l'Eternel, and Martissant Littoral (Fig.…”
Section: Setting and Study Populationmentioning
confidence: 99%
“…GHESKIO was founded in 1982 and is the largest provider of integrated services for HIV and tuberculosis in Haiti. Over the past 35 years, GHESKIO has provided community health interventions in these slum communities including HIV testing, tuberculosis screening, and cholera vaccination [15][16][17]. The study population includes 4 slums: Village de Dieu, Cité Plus, Cité l'Eternel, and Martissant Littoral (Fig.…”
Section: Setting and Study Populationmentioning
confidence: 99%
“…The Luminex spoligotyping method currently used by GHESKIO in combination with the GeneXpert MTB/RIF was adapted as a first-line, high-throughput tool for MTB genotyping in resource-limited countries. Luminex spoligotyping allows real-time typing and can be used for multiple clinical and public health purposes in Haiti, such as epidemiological investigation through community-based active case finding (ACF), contact tracing, and MTB strain characterization during clinical trials of pulmonary MDR-TB treatments [ 23 27 ]. Data from a 2014–2015 retrospective cohort analysis using the GHESKIO ACF campaign revealed that the prevalence of TB and HIV in slums of Port-au-Prince was respectively four and five times higher than national estimates [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Luminex spoligotyping allows real-time typing and can be used for multiple clinical and public health purposes in Haiti, such as epidemiological investigation through community-based active case finding (ACF), contact tracing, and MTB strain characterization during clinical trials of pulmonary MDR-TB treatments [ 23 27 ]. Data from a 2014–2015 retrospective cohort analysis using the GHESKIO ACF campaign revealed that the prevalence of TB and HIV in slums of Port-au-Prince was respectively four and five times higher than national estimates [ 23 ]. Active case finding for TB and HIV should be expanded to other slum populations in Haiti as part of routine programmatic activities to increase the detection rate of TB cases.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, GHESKIO diagnosed 2,437 TB cases and 3,115 HIV cases. 13 The Haitian Group for the Study of Kaposi's Sarcoma and Opportunistic Infections has had designated inpatient treatment capacity for patients with MDR-TB since 2008, with an associated biosafety level three laboratory which serves as a national mycobacteriology reference laboratory for Haiti. Study population. Between June 1, 2008 and December 31, 2015, 252 patients were diagnosed with MDR-TB.…”
Section: Methodsmentioning
confidence: 99%